Identification of Candida species in the clinical laboratory: A review of conventional, commercial, and molecular techniques - Neppelenbroek, Kh; Seó, Rs; Urban, Vm; Silva, S.; Dovigo, Ln; Jorge, Jh; Campanha, Nh (My University, 2013)
In healthy individuals, Candida species are considered commensal yeasts of the oral cavity. However, these microorganisms can also act as opportunist pathogens, particularly the so-called non-albicans Candida species that are increasingly recognized as important agents of human infection. Several surveys have documented increased rates of C. glabrata, C. tropicalis, C. guilliermondii, C. dubliniensis, C. parapsilosis, and C. krusei in local and systemic fungal infections. Some of these species are resistant to antifungal agents. Consequently, rapid and correct identification of species can play an important role in the management of candidiasis. Conventional methods for identification of Candida species are based on morphological and physiological attributes. However, accurate identification of all isolates from clinical samples is often complex and time-consuming. Hence, several manual and automated rapid commercial systems for identifying these organisms have been developed, some of which may have significant sensitivity issues. To overcome these limitations, newer molecular typing techniques have been developed that allow accurate and rapid identification of Candida species. This study reviewed the current state of identification methods for yeasts, particularly Candida species. © 2013 John Wiley & Sons A/S.
Keywords: Candida; Candida albicans; Candida spp; Candidiasis, oral; Pathology, oral